Learning Strategies In The Digital Era - Adi Syaputra; Enung Hasanah (International Journal of Educational Management and Innovation, 2022)
Implementing learning is growing from a traditional face-to-face system to digital-based learning in the digital era. These changes create new problems for education actors, and they especially require digital adaptation capabilities that teachers must do quickly. This study aims to analyze learning strategies in the digital era, especially at 3 Tapung Junior High School, and reveal what factors influence the implementation of learning in the digital era. This research uses a case study method conducted at the school. The data was obtained by using the interview instrument with the teacher. The interviews showed that the school teachers still felt weaknesses in learning in the digital era. However, they overcome the teachers' various advantages and strategies. The teacher in the learning process applies them. In addition, teachers also take advantage of multiple platforms such as WhatsApp groups, google classroom, google meet, power points, and creative videos to increase student activity in learning to improve student learning outcomes in the digital era.